University at Albany President Karen Hitchcock and... - Schmidt, Mark (Digital Media Department Records, 2003)
University at Albany President Karen Hitchcock and Albany Mayor Jerry Jennings speak with Operating Manager of Saratoga Stable Jack Knowlton at a "Breakfast with the Giants" event at the University at Albany. [20002735]